The impact of self-reported health and register-based prescription medicine purchases on re-employment chances: A prospective study - Annemette Coop Svane-Petersen; Sofie Dencker-Larsen (Elsevier, 2016)
In this paper, we investigate the influence of self-reported health and register-based prescription medicine purchases on re-employment chances, and whether these health indicators measure similar aspects of health in this analysis. Data came from a 2006 Danish unemployment survey among a random sample of unemployed individuals enriched with register data (2006-2008, N=1806). The survey participants all received unemployment benefits from the welfare system and had been unemployed for more than 20 weeks at the time of the interview in 2006. We combined these data with longitudinal register data on individual prescription medicine purchases for somatic illnesses and prescription medicine purchases for mental illnesses, information on re-employment and various socio-demographic variables. We conducted binary logistic regression analyses to investigate the impact of self-reported health and prescription medicine purchases measured in 2006 on re-employment chances in 2007 and 2008. Our analyses show that unemployed workers with poor self-reported health and workers who had prescription medicine purchases for mental illnesses were less likely to be re-employed in 2007 and 2008. Furthermore, the impact of both prescription medicine purchases for somatic illnesses and for mental illnesses increased when adding self-reported health to the model although prescription purchases for somatic illnesses became statistically insignificant. The impact of prescription medicine purchases for somatic illnesses was mediated by self-reported health, whilst prescription medicine purchases for mental illnesses was only partly mediated. Finally, SRH seemed a much stronger prediction than prescription medicines. From these results, we propose, when possible, the inclusion of both an indicator of self-reported health and an indicator of mental health in studies on re-employment. Keywords: Self-reported health, Prescription medicine purchases, Somatic illnesses, Mental illnesses, Re-employment, Prospective study, Register data